IMPLEMENTASI MODEL PEMBELAJARAN SAVI MELALUI EKOWISATA EDUKATIF DALAM MENINGKATKAN KESADARAN LINGKUNGAN SISWA ULUMIYAH PARE - Nur Huda; Thoha Putra (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
Education plays a strategic role in fostering students’ environmental awareness amid escalating global ecological challenges. However, environmental learning practices in schools remain largely teacher-centered and theoretical, limiting their impact on students’ attitudes and pro-environmental behaviors. This study aims to analyze the effectiveness of implementing the SAVI (Somatic, Auditory, Visual, Intellectual) learning model through educational ecotourism in enhancing students’ environmental awareness at MA Hasanuddin Pare. A qualitative case study approach was employed. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed thematically. The findings indicate that integrating SAVI with educational ecotourism significantly enhances environmental awareness across three main dimensions. Cognitively, students demonstrated improved conceptual understanding of ecology and sustainability through direct field experiences. Affectively, stronger internalization of environmental values and ecological empathy emerged through participatory activities and reflective discussions. Behaviorally, students exhibited tangible changes, including reducing single-use plastic consumption, practicing waste segregation, and actively participating in school greening programs. This study concludes that multisensory experiential learning through SAVI and educational ecotourism effectively fosters holistic ecological awareness. The model aligns with the framework of Education for Sustainable Development (ESD) and contributes to achieving SDG 4 on quality education oriented toward sustainable development